HOW WOULD MILLENIAL INVESTORS IMPACT ECONOMIC GROWTH IN INDONESIA? - Nasution, Lia Nazliana; Rusiadi, Rusiadi; Efendi, Bakhtiar; Hendrizal, Feri (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Economic growth is closely related to increasing the production of goods and services in community economic activities. Realizing economic growth requires substantial costs, so the way to achieve economic growth is to increase investment. This study aimed to determine the effect of millennial investors, investment, e-money, inflation, and interest rates in the short, medium, and long term on economic growth in Indonesia. This study uses the VAR technique using the Eviews 10.0 application. Methods and analysis techniques are carried out with the following stages: VAR Model, Impulse Response Function (IRF) model, and Forecast Error Variance Decomposition (FEVD) Model with Assumption Test. The results show that the investment itself recommends short-term investment. In contrast, the other variables, namely Millennial investors, E-money, GDP, Inflation, and Total Investment, do not respond at all, where the response of these variables only appears in the second period. In the medium term, recommended investment itself. Other variables that have the most considerable influence on investment as a policy variable other than the investment itself are Total Investment, then Inflation, Millennial Investors, GDP, and E-money. In contrast, the minor influencing investment is GDP. In the long run, they were recommended by the investment itself.